Growth and photosynthetic characteristics of kailan (Brassica oleraceae var. Alboglabra) grown under LED and flourescent lights - Hamidon, Nurul Amira (2015)
Light-emitting diode (LEDs) have tremendous potential and advantages over traditional forms of horticultural lighting. Their small size, durability, long lifetime, cool emitting temperature, and the option to select specific wavelength for a targeted plant response make LEDs more suitable for plant-based uses than many other light sources. Previous study have demonstrated that the combination of red and blue LED light was effective light source for plant growth and development, and the light spectra, intensities, and durations can easily controlled by growers in artificial growing environments. Therefore, the goal of this study was to evaluate the effects of irradiation with different intensities on the growth and photosynthetic characteristics of kailan (Brassica oleraceae var. Alboglabra). The experiment was conducted at the Physiology Laboratory, Department of Crop Science, Faculty of Agriculture using kailan as the plants material. Plant was cultured in plug tray, installed in the plastic container with 16 hour photoperiod at about 20-25⁰C and humidity 60-70% under fluorescent light (238.68 μmol/m²/s), red and blue light (171.54 μmol/m²/s and 187.00 μmol/m²/s) and red and white (107.69 μmol/m²/s). This experiment was conducted in a randomized complete block design (RCBD) with 4 replications. Experiment gave positive results on the number of leaves, partitioning of dry weight, light response curve and net CO2 assimilation rate-intercellular CO2 concentration curve of kailan plants which was grown under high light intensity of red and blue light treatment and also under fluorescent light was higher than kailan plants grown under low light intensity especially in terms of the leaf photosynthesis characteristics of the plants. Kailan plants grown under red and white LED light show higher plant height compared to other treatment because red irradiance was essential for stem elongation. Therefore, it shows that plants absorb light directly from the irradiance source so that it can be used for plant photosynthesis and photomorphogenesis. It was also shows that the supplemental light quality can be used to enhance the nutritional value and growth of kailan plant.